GREEN SYNTHESIS NANOPARTIKEL PERAK DENGAN BANTUAN GELOMBANG ULTRASONIK: MINI REVIEW - Atika Aulia Ahmad; Noor Hindryawati; Irfan Ashari Hiyahara (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2022)
Silver nanoparticles are particles composed of silver oxide with a size of 1-100 nm that can be made by the bottom-up method through the reduction of Ag+ ions with the addition of a bioreductors and ultrasonic waves. Green Synthesis is currently very popular in the fields of science, technology and industry because it is more environmentally friendly. The use of ultrasonic waves in this synthesis can help to time-efficient and increase the reaction rate. Thus, the purpose of this review is to determine the characteristics of nanoparticles synthesized using ultrasonic waves based on UV-Vis and TEM spectroscopic data. The results of the literature show that the factors that affect the stability of the nanoparticles include the molar concentration of AgNO3, the volume of the extract, the stabilizing agent and the reaction time. The change of Ag+ to Ag0 was shown qualitatively by changing the color of the solution from clear/light yellow to brown. Wavelength values of typical nanoparticles appear at 420-440 nm. In the presence of ultrasonic waves it can produce AgNPs sizes between 8 - 33.8 nm and spherical and uniform nanoparticle shapes